TEATER SEBAGAI MEDIA KOMUNIKASI PENDIDIKAN - Jaeni Wastap (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2019)
Theater performances in Indonesian society today are enjoyed by the audience only as “performances” in general, but have not been interpreted as knowledge space, learning space, self-maturing space or as an educational medium. This study aims to show that theater is a medium of educational communication that can be held through the earliest levels of education to higher education and become a space for education for the wider community. The method used in this study is a qualitative research method. In collecting data using observation and in-depth interviews and continued with interactive analysis. The research subjects that were observed and made the speakers were kindergarten (TK) teachers in Cirebon and Bandung, junior / senior high schools in Cirebon and Bandung, and instructors (students) theater in art colleges (ISBI Bandung), as well as communities in Cirebon and Bandung that use theater media in the learning process. The results of this research show that theater as a performing art is essentially a medium of communication. The conclusions of the results of this study indicate that theater must be understood as an institution, media, and part of the communication process in exploring knowledge, exchanging knowledge, and utilizing the knowledge gained.